Models for inferring evaporation from meteorological measurements - Nunn, John R. (John Robert), 1944-, author; Bledsoe, L. J. (Lewis Jackson), 1942-, author; Burman, Robert D., author; Colorado State University, Natural Resource Ecology Laboratory, publisher (Colorado State University. Libraries, 1970)
Methods for prediction of evaporation to correct measured precipitation data.
January 1970.
Keywords: Precipitation (Meteorology) -- Measurement; Precipitation gauges; Meteorology -- Statistical methods; Evaporation (Meteorology)